COMMUNICATING AND EVALUATING LANDSCAPE DESIGN CONCEPTS ONLINE WITH A VIRTUAL REALITY LANDSCAPE MODEL - Akhmad Arifin Hadi; Einar Kretzler; Barty Warren Kretzschmar (http://arl.faperta.ipb.ac.id/, 2012)
The communication between designers and users is needed in order to maintain a high level of engagement among the public participants, especially incase study which is considering the environment. The objective of this research is to investigate if visualization by using Virtual Reality (VR)model is suitable media to communicate landscape design idea from designer to public (users) in case study Situ Leutik Lake. It is answer the question if VRmodel combined with online questionnaire can be a method to gather public participation in landscape design process for case study which is related with public and environments.The research is started by creating three designalternatives of Situ Leutik Lake in VR model by using Quest 3D. The next step is obtaining public feedback about VR model and selecting the most preferred landscape design alternative. Respondents are asked to investigate three design alternatives by doing walkthrough and bird view in the VR model. After operating VR model, users are asked to fulfill the online questionnaire. In online questionnaire, respondents are asked if they understand about the idea of each design alternatives. Respondents are also asked to select the most preferred design alternative and give suggestions about final design.The results show that respondents understand about ideas of each landscape design alternatives and agree that VR model can be media to communicate landscape design idea. The next result is that landscape design alternative number 3 is the most preferred landscape design chosen by respondents. The feedback from respondents about proposed site is supported the statement of Sheppard et al (2008) that visioning by using VR model can affect awareness, emotion and motivation of community to their environment. For site case which involving publics and considering sustainability of environment, the use of VR model is very useful for giving a good understanding to stakeholders about ideas of landscape designer.